(untitled) (Pedagogy of Higher and Secondary Education, 2004)
The article investigates the problem of developing students creative abilities in terms of project work This type of the activity enables a teacher to solve not only the problem of student talking and better quantity and quality of the language used in class but developing students ’ creative abilities as well.